A new species of Harpagobaetis Mol, with amended diagnosis of the genus, and new considerations on predatory species of Baetidae (Ephemeroptera) from South America - Cruz, Paulo Vilela; Hamada, Neusa (Zootaxa, 2019)
A remarkable new predatory species of Baetidae was collected in a relict patch of Amazonian savanna in Brazil. The feeding habit of the nymph of this new species is very rare in mayflies. Baetidae is composed of more than 900 species, but only 12 are considered to be predators; in South America, the only species recognized as a predator is Harpagobaetis gulosus Mol 1986. The objectives of this study are to describe Harpagobaetis brigada sp. nov., based on nymphs and to amend the diagnosis of the genus. The predatory habit of the nymphs of the new species was confirmed by gut-content analysis and by direct observations of behavior. Based on similar morphological adaptations, we hypothesized that Adebrotus lugoi Salles, 2010 possesses predatory habit. Harpagobaetis brigada sp. nov. can be classified as psammophilous, inhabiting a threatened stream in a relict patch of savanna in southern Amazonia. Based on these characteristics, we recommend evaluation of this new species to identify its conservation status and to contribute to the assessment of the state of conservation of the Brazilian fauna.